Special Issue “Wearable Augmented and Mixed Reality Applications” - Andrea Sanna; Federico Manuri; Francesco De Pace (Information, 2019)
Until some years ago, there was a lack of affordable devices that allowed for research in order to design and implement augmented and mixed reality applications. Thanks to technology improvements, it is now possible to find several wearable devices on the market that greatly improve the synergy between the real and virtual world, thus allowing users to be part of an immersive experience in which they can easily interact with 3D assets and real objects at the same time. Thus, the number of augmented reality and mixed reality (AR/MR) applications is greatly increased, from educational or cultural heritage applications to industry ones, such as maintenance-assembly-repair processes or product inspection and building monitoring. Indeed, several improvements have been made in order to enhance this technology, but some issues still need to be tackled, namely: limited field-of-view, tracking stability, the effectiveness of user interfaces to interact with 3D contents, and many others.